Analyses of Avascular Mutants Reveal Unique Transcriptomic Signature of Non-conventional Endothelial Cells - Pak, Boryeong; Schmitt, Christopher E.; Choi, Woosoung; Kim, Jun-Dae; Han, Orjin; Alsiö, Jessica; Jung, Da-Woon; Williams, Darren R.; Coppieters, Wouter; Stainier, Didier Y. R.; Jin, Suk-Won (Frontiers in Cell and Developmental Biology, 2020)
Endothelial cells appear to emerge from diverse progenitors. However, to which extent their developmental origin contributes to define their cellular and molecular characteristics remains largely unknown. Here, we report that a subset of endothelial cells that emerge from the tailbud possess unique molecular characteristics that set them apart from stereotypical lateral plate mesoderm (LPM)-derived endothelial cells. Lineage tracing shows that these tailbud-derived endothelial cells arise at mid-somitogenesis stages, and surprisingly do not require Npas4l or Etsrp function, indicating that they have distinct spatiotemporal origins and are regulated by distinct molecular mechanisms. Microarray and single cell RNA-seq analyses reveal that somitogenesis- and neurogenesis-associated transcripts are over-represented in these tailbud-derived endothelial cells, suggesting that they possess a unique transcriptomic signature. Taken together, our results further reveal the diversity of endothelial cells with respect to their developmental origin and molecular properties, and provide compelling evidence that the molecular characteristics of endothelial cells may reflect their distinct developmental history.